Effects of Substorms on High‐Latitude Upper Thermospheric Winds. Issue 1 (18th January 2021) - Zou, Ying; Lyons, Larry; Conde, Mark; Varney, Roger; Angelopoulos, Vassilis; Mende, Stephen
Abstract: During magnetospheric substorms, high‐latitude ionospheric plasma convection is known to change dramatically. How upper thermospheric winds change, however, has not been well understood, and conflicting conclusions have been reported. Here, we study the effect of substorms on high‐latitude upper thermospheric winds by taking advantage of a chain of scanning Doppler imagers (SDIs), THEMIS all‐sky imagers (ASIs), and the Poker Flat incoherent scatter radar (PFISR). SDIs provide mosaics of wind dynamics in response to substorms in two dimensions in space and as a function of time, while ASIs and PFISR concurrently monitor auroral emissions and ionospheric parameters. During the substorm growth phase, the classical two‐cell global circulation of neutral winds intensifies. After substorm onset, the zonal component of these winds is strongly suppressed in the midnight sector, whereas away from the midnight sector two‐cell circulation of winds is enhanced. Both pre and postonset enhancements are ≥100 m/s above the quiet‐time value, and postonset enhancement occurs over a broader latitude and local‐time area than preonset enhancement. The meridional wind component in the midnight and postmidnight sectors is accelerated southward to subauroral latitudes. Our findings suggest that substorms significantly modify the upper‐thermospheric wind circulation by changing the wind direction and speed and therefore are important for the entire magnetosphere‐ionosphere‐thermosphere system. Key Points: Scanning Doppler imagers allow us to study the substorm effect on high‐latitude upper thermospheric winds in 2D as a function of time Winds show strong latitudinal and local time dependence. During the growth phase, the classical two‐cell circulation of winds intensifies After substorm onset, in the midnight sector the zonal wind is suppressed, whereas away from the midnight two‐cell circulation is enhanced